PENDAMPINGAN PEMBELAJARAN KITAB UYUNUL MASAIL DI DUSUN KRUTUK SELAMA MASA PANDEMI - Arina Ulfatul Maula; Dzulfikar Sholeh (Institut Agama Islam Syubbanul Wathon Magelang, 2021)
This empowerment aims to develop the assets of the Nibrosul Athfal Madrasah Institution and the routine recitation of mothers to find the right method and time to solve the problems of menstruating, postpartum, and istihadloh during the Covid-19 pandemic. The method used in this study uses the ABCD (Asset Based Community Development) method. The important stages in ABCD are Define, Discovery, Dream, Design, and Destiny. The data collection technique used in this study was by means of interviews, observation, and documentation obtained as a result of research in completing the task of KKN-PMD IV. Based on the results of the questionnaire given, it shows that the mentoring activities for learning the book of Uyunul Masail are going well and can be designated as permanent learning. And with the assistance and development of the Uyunul Masail book learning method, it can make a good change for the understanding of the residents of Krutuk Hamlet regarding the discussion of menstruation, postpartum, istihadloh and thoharoh.